1998
DOI: 10.1128/mcb.18.3.1190
|View full text |Cite
|
Sign up to set email alerts
|

The Saccharomyces cerevisiae RAD9 Checkpoint Reduces the DNA Damage-Associated Stimulation of Directed Translocations

Abstract: Genetic instability in the Saccharomyces cerevisiae rad9 mutant correlates with failure to arrest the cell cycle in response to DNA damage. We quantitated the DNA damage-associated stimulation of directed translocations in RAD9؉ and rad9 mutants. Directed translocations were generated by selecting for His ؉ prototrophs that result from homologous, mitotic recombination between two truncated his3 genes, GAL1::his3-⌬5 and trp1::his3-⌬3::HOcs. Compared to RAD9 ؉ strains, the rad9 mutant exhibits a 5-fold higher r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
1
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 74 publications
5
57
1
1
Order By: Relevance
“…We combined our data for MMS and HU sensitivity with the reported data for UV and IR sensitivity to cluster the MMS-sensitive mutants on the basis of their cross-sensitivity to UV, IR, and HU (Table 2). Because both these genome-wide studies missed known UV-or IR-sensitive mutants, we supplemented the data with literature reports (4,5,49,(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62). We noted several interesting properties of these mutants.…”
Section: Resultsmentioning
confidence: 99%
“…We combined our data for MMS and HU sensitivity with the reported data for UV and IR sensitivity to cluster the MMS-sensitive mutants on the basis of their cross-sensitivity to UV, IR, and HU (Table 2). Because both these genome-wide studies missed known UV-or IR-sensitive mutants, we supplemented the data with literature reports (4,5,49,(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62). We noted several interesting properties of these mutants.…”
Section: Resultsmentioning
confidence: 99%
“…The DNA damage checkpoint gene RAD9 is required for efficient utilization of some repair pathways (Fasullo et al, 1998). A RAD9-dependent midanaphase delay has been observed in yeast cells containing a dicentric chromosome, but loss of this gene does not adversely affect strain viability (Table 1) (Yang et al, 1997).…”
Section: Dicentric Chromosome Repair Requires Rad1mentioning
confidence: 99%
“…The checkpoint adaptor Rad9 functions in SCR: Using genetic assays based on his3 truncated genes it has been proposed that Rad9 promotes DSB repair by SCR (Fasullo et al 1998) and genetic studies of DNA damage sensitivity have placed DOT1 in the RAD9 epistasis group (Wysocki et al 2005;Conde and SanSegundo 2008). In addition, it has been reported that Dot1-mediated histone H3K79 methylation is required for the recruitment of the Rad9 checkpoint adaptor protein to an irreparable HO-induced DSB at the chromosomal MAT locus (Wysocki et al 2005).…”
Section: Dot1 Contributes To Efficient Scrmentioning
confidence: 99%